Scientific Reinvestigation Of The Rock Art At Gua Tambun, Perak - Siang, Noel Hidalgo Tan Suwi (2010)

(untitled)
This study presents the findings of the latest research conducted at the rock art site of Gua Tambun, in Perak, Malaysia. Gua Tambun is a rock shelter overlooking the city of Ipoh and it contains numerous paintings including depictions of wildlife and human forms in various shades of red, orange and purple. However, since its initial ‘discovery’ some 50 years ago, little research has been carried out at Gua Tambun because of the traditional difficulties in investigating and understanding rock art. The aims of this study is to expand the current knowledge about the rock art at Gua Tambun by creating a record and inventory of the site; conduct investigations into the nature of the rock pigments used to create the paintings; make comparisons with other rock art in the region, particularly in Southern Thailand to seek similarities in form; and to determine the date, technology and authorship of the rock art. Where early reports have estimated the number of 50-80 paintings present at the site, a staggering 640 individual rock art elements were recorded and catalogued, many of which were barely visible to the naked eye. Data on each of the 640 elements is presented in Volume 2 of this study. In addition, rock art was also found in many other smaller panels distributed along the walls of the shelter that were previously not reported. Analysis of the pigments confirmed an early assumption that at least some of the rock art were painted using haematite of local origin.